Contemporary Pastoralism: Old Problems. New Challenges - Khazanov, A.М. (Хазарский альманах, 2007)
In all probability, in the foreseeable future, spatial mobility will remain an important characteristic of stock breeding in many arid environments. The general trend in pastoralists’ development will be connected with the growing commercialization of production, introduction of modern livestock technology, the better definition of property rights, and, in some cases, even the introduction of private land tenure. Some pastoralists will benefit from This process will continue to be very painful, and will bring a lot of resentment. Perhaps, it is possible to somewhat alleviate its negative collateral effects, but hardly to avoid them completely. However, eventually mobile pastoralism should become more efficient and more productive along the lines of the capitalist economic efficiency.